Physicochemical and Organoleptic Characteristics of Pomegranate (Punica granatum) Prebiotic Mellorine: The Effect of Pomegranate Juice Concentration and Inulin Addition - Niswa Indirajati; Rosida Rosida; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Mellorine is a frozen dessert with characteristics similar to ice cream but containing a lower fat content. The incorporation of pomegranate is intended to enhance its nutritional value. Pomegranate (Punica granatum) is recognized as a potential functional food due to its high content of bioactive compounds and health benefits, including antioxidant, antimicrobial, and anti-inflammatory activities. Inulin is a soluble dietary fiber that benefits the host by stimulating the growth of beneficial bacteria, such as Lactobacillus and Bifidobacterium. This study aimed to determine the effects of pomegranate juice concentration and the addition of inulin on the physicochemical and sensory characteristics of prebiotic pomegranate mellorine, and to identify the best treatment to produce optimal product characteristics and consumer acceptability as a functional mellorine. Variations in pomegranate juice concentration and inulin addition were applied. The physicochemical parameters included crude fiber, vitamin C, viscosity, overrun, total soluble solids, and melting time, while sensory attributes included color, aroma, taste, and texture. The results showed that pomegranate juice concentration and inulin addition significantly affected several characteristics of prebiotic pomegranate mellorine. The best treatment, consisting of 75% pomegranate juice and 6% inulin, produced mellorine with 0.34% crude fiber, 15.97% vitamin C, 218.25 mPa·s viscosity, 39.01% overrun, 27.75 °Brix total soluble solids, and a melting time of 20.04 minutes, with favorable sensory acceptance. Further analysis showed 3.16% dietary fiber, 2.95 × 10? CFU/mL prebiotic activity, 4.71% fat, and 23.12 mg/100 g anthocyanin.Top of FormBottom of Form Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungeSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production